2021
DOI: 10.1038/s41598-020-79227-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small ridge and furrow mulching degradable film on dry direct seeded rice

Abstract: Global climate change and socio-economic development have led to a shortage of water and labour resources, which has had a significant impact on rice cultivation. In this study, the application of micro-ridge-furrow planting technology and degradable film mulching in dry direct-seeded rice was investigated to address the factors restricting the development of the rice industry and reduce the impact of rice production on the environment. The effects of a micro-ridge-furrow planting pattern and degradable film m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The shallow soil layer of salt accumulates towards the ridge top, while the moisture increases with the decrease in elevation. The low-salt and high-moisture environment in the furrow creates relatively suitable water and salt conditions for crop growth [19].…”
Section: Introductionmentioning
confidence: 99%
“…The shallow soil layer of salt accumulates towards the ridge top, while the moisture increases with the decrease in elevation. The low-salt and high-moisture environment in the furrow creates relatively suitable water and salt conditions for crop growth [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the accumulated temperature of soil covered with ordinary films is significantly higher than that of soil mulched with black films [18,19]. The warming effect of novel mulching materials before degradation, such as biodegradable and liquid films, barely differs from that of ordinary plastic films [20][21][22]. The timely peeling of films during crop growth can effectively abate the phenomenon of crop premature senescence caused by high temperatures [23][24][25].…”
Section: Introductionmentioning
confidence: 99%